Developing Strategy For 21st Motoring - Raedi, Muhammad; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2015)
On the making a non-dealer car service station business was already been the owner of 21st Motoring’s head at 25 years age, when he was still working at Ford Motor Company. However, 21st Motoring has already run for 2 years which having a hard time to attract new customers, although 21st Motoring has a strong quality on its business with having a standardize of its works and having sufficient tools. In the face of the business issues that needed some methods, they are conducting external assessment by PEST Analysis and Five Forces Porter’s Analysis, and internal assessment by Value Chain Analysis and Existing Business Model Canvas. Then SWOT Analysis is used to conclude both external and internal analysis. SPACE Matrix is used to find the suitable company strategy for 21st Motoring. After analyzing, Competitive Strategy is the right strategy for 21st Motoring which should be pursued, with 2 strategies within it, they are Intensive Strategy and Integrative Strategy. To find the best strategy which should be focused between those 2 strategies, QSPM calculation has to be developed. And the result of that is Intensive Strategy, which are Market Penetration, Market Development and Product Development. Next step will be using a Diamond strategy to propose a business strategy. For the next stage analysis has to be developed by using TOWS Matrix to make a functional strategy within the business. After that, the result of TOWS Matrix will be implemented to the New Business Model Canvas for the propose of new strategies. Keyword: business strategy, car service station, business model canvas